2020
DOI: 10.1111/ajt.15750
|View full text |Cite
|
Sign up to set email alerts
|

The economic burden of kidney graft failure in the United States

Abstract: Despite improvements in outcomes for kidney transplant recipients in the past decade, graft failure continues to impose substantial burden on patients. However, the population‐wide economic burden of graft failure has not been quantified. This study aims to fill that gap by comparing outcomes from a simulation model of kidney transplant patients in which patients are at risk for graft failure with an alternative simulation in which the risk of graft failure is assumed to be zero. Transitions through the model … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…Sussell et al have shown that, despite improvements in outcomes for kidney transplant recipients in the past decade, graft failure continues to impose substantial burden on patients (Sussell et al 2020 ). In this study, authors compared outcomes from a simulation model of kidney transplant patients, in which patients who were at risk for graft failure were compared with an alternative simulation in which the risk of graft failure is assumed to be zero.…”
Section: The Burden and Cost Of Allograft Rejectionmentioning
confidence: 99%
“…Sussell et al have shown that, despite improvements in outcomes for kidney transplant recipients in the past decade, graft failure continues to impose substantial burden on patients (Sussell et al 2020 ). In this study, authors compared outcomes from a simulation model of kidney transplant patients, in which patients who were at risk for graft failure were compared with an alternative simulation in which the risk of graft failure is assumed to be zero.…”
Section: The Burden and Cost Of Allograft Rejectionmentioning
confidence: 99%
“…The median length of hospital stay of 25 days in this trial was in line with the data originated in China 46 , 47 but appeared much longer than that in the US and European countries. 48 , 49 , 50 This difference may be attributed to the different health care systems in various countries. Fourth, as a single-center trial based on controlled donors after cardiac death and characterized by a relatively short warm ischemic time, the generalizability of its findings should be tested in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…In the kidney transplant literature multistate models have mainly, but not exclusively, been applied in studies of outcomes of waitlisted patients. 25 , 26 , 27 , 28 They are a natural fit here, because waitlisted patients can transition between several different states (e.g., listed active, listed inactive, death on the waitlist, removed from waitlist, transplanted). Multistate models can also be a useful adjunct to traditional survival analyses in several ways.…”
Section: Discussionmentioning
confidence: 99%